Bout duration and number of players of soccer small-sided games affect perceived enjoyment, physiological responses, and technical-tactical performance. Issue 4 (2nd October 2022) - Farhani, Zouhaier; Hammami, Raouf; Gene-Morales, Javier; Chortane, Sabri Gaied; Bouassida, Anissa; Juesas, Alvaro; Colado, Juan C.
ABSTRACT: Purpose: To compare perceived enjoyment (PE), % of heart rate peak (%HRpeak), blood lactate (La), rating of perceived exertion (RPE), and technical-tactical performance of soccer players after four-a-side (4vs4) and three-a-side (3vs3) small-sided games (SSGs) with goalkeepers. Methods: Sixteen males (20.7 ± 0.7 years; experience: 6.9 ± 1.2 years) completed and were measured after six sessions of SSGs (one twelve-minute bout (1x12), two six-minute bouts (2x6), and three four-minute bouts (3x4), both 3vs3 and 4vs4). Repeated measurements ANOVA evaluated significant differences ( p ≤ 0.05). Results: There was higher PE for 1 × 12 compared to 2 × 6 (effect sizes [ES] = 1.53 [3vs3 and 4vs4]) and 3 × 4 (ES = 3.13 [4vs4] and 4.16 [3vs3]). Continuous bout duration (1x12) was characterized by a significantly greater percentage of successful passes compared to 2 × 6 (ES = 2.57 [4vs4] and 1.79 [3vs3]) and 3 × 4 (ES = 2.14 [4vs4] and 1.73 [3vs3]), and minor ball loss rate (2x6: ES = 2.14 [4vs4] and 1.11 [3vs3]; 3x4: ES = 2.11 [4vs4] and 1.57 [3vs3]). The percentage of successful tackles was only significantly greater for 1 × 12 in 4vs4 (ES = 0.83 [2x6] and 0.86 [3x4]) and successful duels in 3vs3 (ES = 1.41 [2x6] and 1.43 [3x4]). Significantly greater %HRpeak for 1 × 12 compared to 2 × 6 (ES = 1.02 [4vs4] and 0.81 [3vs3]) and 3 × 4 (ES = 1.04 [4vs4] and 0.99 [3vs3]) was observed, La differences were only significant in 3vs3 (ES = 1.60 [2x6] and 1.30 [3x4]). Greatest RPE were encountered in 3 × 4 (4vs4) and 1 × 12 and 3 × 4 (3vs3). Significant differences existed between the 3vs3 and 4vs4 designs with a non-clear pattern of better results for neither of both. Conclusion: Therefore, coaches should consider longer continuous bouts when programming SSGs-based training to significantly increase PE, technical-tactical performance, and training load.